The right to privacy in digital era: brief considerations. - DOI 10.5935/2448-0517.20190064 - González, José Alberto Rodríguez Lorenzo; d’Aguiar, Filipa Pais (Juris Poiesis - Qualis A3, 2020)
The AI presence in everyday life, in the most diverse ways, both represents a world of endless opportunities than ever before in world history and, simultaneously, countless risks rising from its use. Hence, it urges for a brief pondering on one of the main challenges of digital era, i.e., the right to privacy scope. Therefore, starting from the analysis of the right to privacy in national, European and international levels, this article intends to ponder on the framing of the right to privacy in digital era considering, in this context, the main challenges emerging from AI use, the current legislation and the multidisciplinary approaches contributions. For this research, it was used the deductive and hypothetical-deductive approach methods as well as the historical, comparative and monographic procedure methods (Markoni & Lakatos, 2007).